2021
DOI: 10.1088/1361-6528/abfe8e
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvements in all-solution processed inverted QLEDs realized by inserting an electron blocking layer

Abstract: Highly efficient, all-solution processed inverted quantum dot light-emitting diodes (QLEDs) are demonstrated by employing 1,3,5-tri(m-pyrid-3-yl-phenyl)benzene (TmPyPB) layer as electron blocking layer. Electron injection from ZnO electron transport layer to quantum dots (QDs) emission layer (EML) can be adjusted by thickness of TmPyPB layer, enabling the balanced charge carriers in QDs EML. With optimal thickness of this TmPyPB adjuster, 59.7% increment in the device current efficiency (from 8.2 to 13.1 cd A−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Besides reducing the electron transport, increasing the hole mobility of a HTL by introducing a proper doping material is a reasonable option. Previously, it was found that the photoluminescence (PL) properties and stability of QDs were improved after encapsulating QDs in NaCl crystals . In the current study, we investigated the effect of NaCl on atmosphere-process-based EL QLEDs and found that the salt also benefits the carrier mobility of poly­(vinylcarbazole) (PVK), a conductive polymer generally used as an HTL in EL QLEDs, as shown in Figure .…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Besides reducing the electron transport, increasing the hole mobility of a HTL by introducing a proper doping material is a reasonable option. Previously, it was found that the photoluminescence (PL) properties and stability of QDs were improved after encapsulating QDs in NaCl crystals . In the current study, we investigated the effect of NaCl on atmosphere-process-based EL QLEDs and found that the salt also benefits the carrier mobility of poly­(vinylcarbazole) (PVK), a conductive polymer generally used as an HTL in EL QLEDs, as shown in Figure .…”
Section: Resultsmentioning
confidence: 86%
“…In general, the mobility of the electron-transport layer (ETL) is higher than that of the hole-transport layer (HTL) in QLED devices, which can cause the carrier imbalance in the QD layer and thus reduce the device performance. There are two possible ways to sort out the problem: (1) the reduction of electron transport by applying an electron blocking layer and (2) the introduction of a high hole mobility additive such as poly­(9,9-dioctylfluorene- alt - N -(4- s -butylphenyl)­diphenylamine) or poly­[bis­(4-phenyl)­(4-butylphenyl)­amine] in a HTL to enhance the hole mobility. For the first method, the hole injection and mobility problems are simply negligible, and the overall carrier mobility of the devices decreases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CP solution is prepared via the solution blending technique. 12 In this technique, the CPs are dissolved in a suitable solvent to reach the homogenous distribution of all the CPs throughout the thin film surface. Different solvents were used to prepare the CP solutions, such as toluene and chloroform.…”
mentioning
confidence: 99%